3D Printed PLA/PCL/TiO2 Composite for Bone Replacement and Grafting. (23rd April 2018) - Nájera, Sandra E.; Michel, Monica; Kim, Nam-Soo
ABSTRACT: Polymer composites of Polylactic acid (PLA) and poly-ε-caprolactone (PCL), containing small amounts of titanium oxide (TiO2 ) were developed for biomedical applications. These composite materials were prepared, and then printed using Fused Deposition Modeling (FDM). 3D printed structures were characterized to determine their mechanical properties and biocompatibility. DSC analysis yielded useful information regarding the immiscibility of the different polymers, and it was observed that the particles of TiO2 improved the stability of the polymers. The ultimate tensile strength and the fracture strain increased by adding TiO2 as a filler, resulting in values of approximately 45 MPa and 5.5 % elongation. The printed composites show excellent in vitro biocompatibility including cell proliferation and adhesion, and are therefore promising candidates to be used in the biomedical field for bone replacement procedures, due to their properties similar to those of cancellous bone.